A biochemical and histopathological evaluation of generalized pulp calcification in young permanent teeth - S K Bahetwar; Ramesh Kumar Pandey; Rajeev Kumar Singh; T S Bahetwar; Ali Wahid (Wolters Kluwer Medknow Publications, 2012)
Pulp calcifications are a frequent finding on bitewing and periapical radiographs in older age-groups but their occurrence in the entire dentition in young subjects is unusual. We report such an unusual occurrence of generalized pulp calcification in a 13-year-old Indian female. Radiographic examination of the dentition revealed pulp calcifications in all permanent teeth, located mostly in the pulp chamber but with some in the root canals. The patient's dental, medical, and family history was noncontributory. Biochemical analysis of the removed pulp calcification from one of the teeth during endodontic treatment showed large amounts of calcium, phosphorus, and carbonate. However, metabolic evaluation of patient through liver and kidney function tests and other blood investigations did not reveal any metabolic disorder. The patient was also evaluated for any systemic, syndromic, or genetic involvement but this was also noncontributory. Therefore, we propose that this unusual case of generalized pulp calcification is of idiopathic origin. In this work, histopathological and biochemical evaluations of the pulp calcification was done to try and understand the initiation and progress of calcifications in pulpal tissue.